Dark Mode

5,248 views

13 votes

Best answer

$A. \ \ (p \vee q) \rightarrow p$

$\quad \quad \equiv \ \ \neg(p \vee q) \vee p$

$\quad \quad \equiv \ \ (\neg p \wedge \neg q) \vee p$

$\quad \quad \equiv \ \ (\neg p \vee p)\wedge(\neg q \vee p)$

$\quad \quad \equiv (p \vee\neg q)$

$B. \ \ p \vee (q \rightarrow p)$

$\quad \quad \equiv \ \ p \vee (\neg q \vee p)$

$\quad \quad \equiv \ \ (p \vee p)\vee\neg q$

$\quad \quad \equiv p \vee\neg q$

$C. \ \ p \vee (p \rightarrow q)$

$\quad \quad \equiv \ \ p \vee (\neg p \vee q)$

$\quad \quad \equiv \ \ ( p \vee \neg p) \vee q$

$\quad \quad \equiv \ \ T \vee q$

$\quad \quad \equiv \ \ T$

$D. \ \ p \rightarrow (p \rightarrow q)$

$\quad \quad \equiv \ \ p \rightarrow (\neg p \vee q)$

$\quad \quad \equiv \ \ \neg p \vee(\neg p \vee q)$

$\quad \quad \equiv \ \ (\neg p \vee\neg p) \vee q$

$\quad \quad \equiv \ \ \neg p \vee q$

Hence, Option(**C**) $p \vee (p \rightarrow q)$.